Energy Saving Via Accurate Computation of Crude Flow Measurement and Calculations - Siddiq, Hisham I. (Journal of Petroleum Research and Studies, 2024)
Oil industry involves transporting crude oil using pipelines for long distances. One of the major losses factors in this industry is the inaccurate flow calculations. The flow is calculated by pressure differential measurement between two adjacent pumping stations. In addition, there are flow counters at the discharge end of the pipeline. A multi-pumping station oil pipeline, the subject of this case study these two methods seem not to give the same result any more. That’s because of the lack of effective flow factors updating, and the very slow or even no response to sudden unexpected changes in pressure differential in pipeline sections. This paper shows the tremendous effect of these factors and its impact to continuous pumping with proposed empirical formula for updating, for minimal calculation errors and hence related losses.